Einflussfaktoren auf die Pflegebelastung der Angehörigen von Menschen mit Demenz: der Bayerische Demenz Survey (BayDem) - Dietzel, Nikolas; Karrer, Linda; Wolff, Franziska; Kratzer, André; Hess, Manuela; Grässel, Elmar; Kolominsky-Rabas, Peter (Gesundheitswesen, 2020)
Background Dementia is an age-specific disease with increasing care needs over the course of the disease. Care is predominantly conducted by caregivers. Caregiver burden is a core criterion for the evaluation of the care situation. The aims of this examination are to identify predictors of caregiver burden and to analyze the course of the caregiver burden over a 12 months period. Methods The Bavarian Dementia Survey (BayDem) is a supra-regional, longitudinal study carried out at 3 different sites in Bavaria, Germany. Participants were people with dementia (pwd) as defined by ICD-10 and their informal caregivers. Data was collected by standardized face-to-face interviews in cooperation with local actors. For statistical analysis, a multiple regression as well as a mixed ANOVA (Analysis of Variance) and repeated measures ANOVAs were used. Results In this analysis, 295 pwd and 276 caregivers were studied. Key factors influencing caregiver burden were gender of the pwd, behavioral and psychological symptoms and a decline of everyday functioning of the pwd as well as gender of the informal caregivers, their relation to the pwd and if they live at the same household as the pwd. Analysis showed a significant main effect of time over the course of the caregiver burden. Conclusion A permanent high caregiver burden can cause health problems for the caregivers. However, caregivers can be supported according to the specific factors of the caregiver burden. One approach in order to support caregivers could be a combination of pharmacological and non-pharmacological interventions for the treatment of disease-specific symptoms and an empowerment as well as the provision of support services for the caregivers. Furthermore, tailored services for specific target groups can be meaningful.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Burden Scale for Family Caregivers (BSFC-s); caregiver burden; course; dementia; informal caregivers; predictors